Comparative Study on Implementing Home Air Conditioning for Passenger Carriages in the Indonesian Railway - Hardianto Eko Prasetio; Siti Malkhamah; Charles Watson; Subarmono Subarmono (Journal of the Civil Engineering Forum, 2017)
Passenger comfort is important in railway transport system. The train operator company in Indonesia would like to increase passenger comfort by installing home air conditioning into all existing carriages of the economy train. The air conditioning is expected to give better passenger convince. Therefore, the aims of this research are to know the cooling load and compare characteristic between home Air Conditioning (AC) and train AC. The cooling load calculation is analyzed using Cooling Load Temperature Difference (CLTD)/Solar Cooling Load (SCL)/Cooling Load Factor (CLF) method. Comparison between both home air conditioning and train air conditioning are discussed to identify the benefits and drawbacks of each type. The total heat that needs to be removed from a passenger carriage with home AC is 104,334 Btu/h, while the total cooling capacity of home AC is 75,000 Btu/h. The passenger carriages with train AC have cooling capacity 119,100 Btu/h to remove heat 11,5290 Btu/h. The Energy Efficiency Ratio (EER) value of most home AC is higher than train AC, installation time of home AC is shorter than train AC, total cost for 20 years period of home AC is more than train AC. There is no guarantee for home AC, so everything that happens to it will become the full responsibility of train operator company. The train AC control system is more effective than the home AC. No fresh air is permitted to circulate within the home AC system hence, the same air is repeatedly processed in the system. Implementing home air conditioning in the existing passenger carriages is worthwhile for short time period in the goal to increase and improve the level of service provided by giving better comfortability to the passenger.